Democracy Needs a Free Press - Lessner, Cassidy (Maine Policy Review, 2018)
Each year the Margaret Chase Smith Library sponsors an essay contest for high school seniors. The essay prompt for 2018 concerned the importance of a free press. This is the first-place essay, written by Cassidy Lessner.